Developing an Environment-based Textbook for a Poetry Writing Course - Olga Dona Retsi; Maida Norahmi; Susanty Susanty; Sulamit Syeba; Lesly Martha Cecylia Meka; Norhayati Norhayati (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
This study aims to develop a contextual teaching book for contemporary poetry writing that integrates environmental elements and local cultural values while enhancing students’ creative writing skills and appreciation of cultural diversity. Many students struggle to connect poetry to their daily lives because the teaching materials currently used are often general, text-oriented, and insufficiently relevant to their cultural backgrounds. Therefore, this study employs a Research and Development (R&D) approach, adapting the stages of needs analysis, product design, development, expert validation, revision, and limited field testing. Research data were collected through observations, questionnaires, and feasibility assessments conducted by content and media experts, and were analyzed using both quantitative and qualitative descriptive techniques. The developed teaching book integrates natural environments and local cultural values as sources of inspiration for poetry creation, emphasizing themes, diction, metaphors, and imagery that reflect local wisdom while maintaining universal and contemporary relevance. The book also includes guided writing activities, examples of modern poetry, and tasks that encourage students’ observation, reflection, and creativity. Theoretically, this study contributes to enriching literature instruction through a culturally grounded contextual approach. In practice, it provides an alternative teaching resource for teachers and students that can strengthen cultural identity, foster ecological awareness, and enhance critical and creative thinking skills through poetry-writing activities. The developed teaching book is expected to serve as an effective learning medium for creating meaningful learning experiences and producing authentic literary works rooted in students’ local identities